The impact of green policies on local economic performance: Evidence from the EU ETS - Ireri Hernandez Carballo; Gian Maria Mallarino; Marco Percoco (Bocconi University, Centre for Research on Geography, Resources, Environment, Energy and Networks (GREEN), 2025)
Environmental policies such as the European Union Emissions Trading System (EU ETS) raise concerns about their impact on local employment and competitiveness. Yet, existing EU ETS studies focus on firm-level outcomes during the initial phases of the program. We construct a panel dataset of about 900 European provinces across 2008 to 2020 to assess the effects of a significant policy change in Phase 3 of the EU ETS. Specifically, we investigate how the changes in the allocation of free allowances affected local economies in terms of employment, gross value added (GVA) and productivity. By assembling a novel dataset and measuring the net change of paid emissions from Phase 2 to Phase 3 we construct a measure of exposure to the policy change at the NUTS-3 level. Using synthetic difference-in-differences, we find that being more exposed to the EU ETS is associated with a statistically significant contraction of employment and GVA in the more carbon-intensive industries. Our results are complemented with evidence on a sizeable reduction in carbon emissions and mild impact in terms of regional disparities in the European Union.
Keywords: 330; EU ETS; Carbon policies; CO2 Emissions; Regional Economics; Economic Geography